New 2-D interleaving grouping LBC applied on image transmission - Wurod Qasim Mohamed; Marwa Al–Sultani; Haraa Raheem Hatem (Institute of Advanced Engineering and Science, 2021)
The modern technologies of the image transmission look for ultra-reducing of the error transmission in addition to enhancing the security over a wireless communication channel. This paper is applied and discussed two different techniques to achieve these requirements, which are linear block code (LBC) and two-dimensions (2-D) interleaving approach. We investigate a new approach of 2-D interleaving that increases the security of the image transmission and helps to diminution the bit error probability (BER). Using an investigated 2-D interleaving grouping LBC approach on image transmission, the system achieves a higher-security information and a better BER comparing with the other systems. It was done by means of peak signal to noise ratio (PSNR) and histogram analysis tests. Simulation results state these enhancements.